2012
DOI: 10.1007/s11999-011-2116-3
|View full text |Cite
|
Sign up to set email alerts
|

Does Ipsilateral Knee Pain Improve after Hip Arthroplasty?

Abstract: Background Intraarticular hip disease is commonly acknowledged as a cause of ipsilateral knee pain. However, this is based primarily on observational rather than highquality evidence-based studies, and it is unclear whether ipsilateral knee pain improves when hip disease has been treated. Questions/purposes We asked whether (1) hip disease was associated with preoperative ipsilateral knee pain and (2) ipsilateral knee pain would improve after hip arthroplasty. Patients and Methods We retrospectively assessed k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Although biomechanical changes and redistribution of loading of the lower limb were detected after THA or TKA in certain studies [5][6][7][8][9], the in uence of a prior TJA on the subsequent ipsilateral THA or TKA is limited. Consistent with the ndings of the current study, Foucher et al [10] reported no increase in biomechanical loading during gait on the ipsilateral knee after THA.…”
Section: Discussionmentioning
confidence: 99%
“…Although biomechanical changes and redistribution of loading of the lower limb were detected after THA or TKA in certain studies [5][6][7][8][9], the in uence of a prior TJA on the subsequent ipsilateral THA or TKA is limited. Consistent with the ndings of the current study, Foucher et al [10] reported no increase in biomechanical loading during gait on the ipsilateral knee after THA.…”
Section: Discussionmentioning
confidence: 99%
“…This is because studies have shown knee pain to improve after ipsilateral hip arthroplasty. 16 Equip the patient adequately to ensure efficiency of a specialist opinion It is valuable in having the history and examination in the referral letter.…”
Section: Referral To a Specialistmentioning
confidence: 99%
“…Patients with end-stage degenerative or inflammatory arthritis report excellent outcomes after THA or TKA [ 4 ]. However, there is some evidence to suggest loading redistribution and biomechanical changes in the lower limb after THA or TKA [ 5 9 ]. Data concerning the influence of prior THA on the ipsilateral knee joint or ipsilateral TKA remain controversial.…”
Section: Introductionmentioning
confidence: 99%